The Influence of E-Servqual on Customer E-Satisfaction, A Case of A State-Owned Bank - Sindi Budi Emilia; Ridwan Sanjaya (Soegijapranata Catholic University, 2023)
The goal of this study is to determine the influence of e-servqual on customer e-satisfaction. The study took a case in a state-owned bank that has been applied digital service. It focused on a unit located in Semarang and used purposive sampling for selecting the respondents who use the bank’s digital service of particularly BRIMO, QRIS, Brizzi, and SMS Banking. The data from 120 customers was gathered using questionnaire and was analyzed using multiple regression. E-servqual was measured using nine dimensions of efficiency, reliability, responsiveness, personal needs, fulfillment, security/trust, ease of use, site organization, and privacy. The results show that e-satisfaction is significantly influenced by the dimensions of e-servqual. However, of the nine dimensions, only site organization that has a negative effect on e-satisfaction.